Structural Reform Packages, Sequencing, and the Informal Economy - Munkacsi, Zsuzsa; Saxegaard, Magnus (IMF working paper ;, 2017)
This paper explores the macroeconomic impacts of labor and product market deregulation using a small open-economy model with formal and informal markets. We examine both the long-run effects and the transition towards the post-reform equilibrium, while our main focus are reform packages and sequencing. The unofficial sector is a major determinant of the sign, and, in particular, the magnitude of responses. South Africa, an emerging country, is considered when Bayesian estimating the model. Regarding the long run, both labor and product market reforms considerably increase output, although labor market reforms are more successful in decreasing unemployment. Nevertheless, there are short-term costs, for example, a decrease in household consumption, net exports or output, or a decrease in competition. Combining reforms, especially with product market deregulation, are good at reducing short-term costs. Finally, concerning the speed of adjustment, it is usually better to start with a labor market reform.